Protocolos analgésicos post operatorio en Ovariohisterectomia en caninas - Rizzo Suñiga, Julio Ricardo (2021)
A documentary research was carried out with the objective of generating information on post-operative analgesic protocols in Ovariohysterectomy in canines. The research was of a bibliographic documentary type, applying in turn deductive research bases from premises raised previously, for this it was necessary to collect and review data using as sources, scientific articles, degree works, blogs including books published on the web, that have issues related to analgesic protocols used in surgical sterilization processes in dogs. The collection of information was carried out between the months of March and April 2021. This bibliographic research allowed to demonstrate that the correct use of analgesics used in Ovariohysterectomy both in the intraoperative and postoperative stages in canines has a fundamental function to the preservation of both the physical and emotional health of the patient since a correct transition from anesthesia to analgesia can guarantee a more effective recovery. In the same way, it was possible to identify that tramadol becomes the drug most used by professionals as part of the postoperative analgesic therapy of patients since in combinations with other drugs in a multimodal way, better results can be obtained to deal with post-pain pain. surgical.